Investigate the Capability of Applying Hidden Data in Text File: An Overview - Zaidan, A.A.; Zaidan, B.B.; Al-Frajat, Ali K.; Jalab, Hamid Abdullah (Asian Network for Scientific Information, 2010)
The aim of this study is to investigate the methods of steganography using the text file as a cover carrier. The hiding data or Steganography is the art of protecting the information by embedding data in medium carrier, for instants this study illustrates historically this art. The steganography technique has been used mainly to hide secret data within multimedia files and one of used files to hide secret data is the text files. In this study, we have proposed the steganography methods using the text files as a review. The study restricts the weak points of this art by hiding information in text file. As a result of this study, the text based steganography has been discussed and the advantages and disadvantages of using the text file as a cover carrier for steganography has been proposed. © 2010 Asian Network for Scientific Information.